ANALISIS KATA CINTA UANG MENURUT I TIMOTIUS 6:10 SERTA IMPLIKASINYA DALAM MEMBANGUN KOMITMEN MELAYANI - Heryanto (JURNAL TABGHA, 2024)
Money play a very important rule in humans’ life. We can found a lot of crime commited related to money, and some of them involved fighting and even murder. Christians have many different opinions related to money according to their money-understanding. This research has purpose : 1) to analize the understanding of word “love for money” according to 1 Timothy 6:10 in Tabgha Indonesia Bethel Church branch in Tanjungpinang. 2) to analize the implication of “love for money” in Tabgha Indonesia Bethel Church branch in Tanjungpinang 3) to analize ministry commitment building in Tabgha Indonesia Bethel Church branch in Tanjungpinang 4) to analize the understanding of word “love for money” according to 1 Timothy 6:10 and its implication in ministry commitment building in Tabgha Indonesia Bethel Church branch in Tanjungpinang. After the research, writer found that : 1) it is needed to return people’s focus to God, 2) understanding the true meaning of “love for money” according to God’s word is needed, 3) it is important to have a continously personal fellowship with God, 4) good ministry standard is necessary, and 5) should become a good example in home and community.